Air stable high-spin blatter diradicals: non-Kekulé versus Kekulé structures. Issue 22 (4th February 2019) - Hu, Xiaoguang; Zhao, Lei; Chen, Hanjiao; Ding, Yousong; Zheng, Yan-Zhen; Miao, Mao-sheng; Zheng, Yonghao
Abstract : 1, 2, 4-Benzotriazinyl based stable diradicals possess singlet ground states and small singlet–triplet energy gaps with a thermal accessible triplet excited state. Abstract : Air stable high-spin diradicals under ambient conditions are relatively rare. We report two 1, 2, 4-benzotriazinyl based diradicals, non-Kekulé o -DBT and Kekulé p -DBT, with a highly twisted bridge. The studies of magnetic susceptibilities reveal that both diradicals possess singlet ground states and small singlet–triplet energy gaps (Δ E s–t = −0.21 and −0.18 kcal mol −1 for o -DBT and p -DBT, respectively), leading to a thermal accessible triplet excited state. Furthermore, variable-temperature electron spin resonance discloses that the average distance between the two spin centers of o -DBT and p -DBT increases with increasing temperature. Finally, both diradical molecules show very high stabilities under high power irradiation and thermal treatment. In particular, the powder of o -DBT exhibits excellent thermal stability up to 270 °C without noticeable decomposition.